2018
DOI: 10.1515/tjj-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Jet Flow Control Using Semi-Circular Corrugated Tab

Abstract: This investigation aims to present the jet mixing characteristics and thrust variations of the subsonic jet employed with plain triangular tab and semi-circular corrugated tab by numerical simulation. A triangular tab with semi-circular corrugations is used in this regard at the exit plane of a convergent nozzle, to study the behavior of the jet and its structure. The near jet flow field is studied for different Mach numbers of 0.6, 0.8 and 1, and the comparisons were done for the jet employed with plain trian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Then the conditions for inlet, tabs, nozzle, domain and outlet are fed. Shear stress transport model is chosen (Kumar and Chidambaram, 2018;Sathish et al, 2021aSathish et al, , 2021b. The solution for jet flow control is chosen and required discretized equation is then being selected from the solution control for solving.…”
Section: Solver Settingsmentioning
confidence: 99%
“…Then the conditions for inlet, tabs, nozzle, domain and outlet are fed. Shear stress transport model is chosen (Kumar and Chidambaram, 2018;Sathish et al, 2021aSathish et al, , 2021b. The solution for jet flow control is chosen and required discretized equation is then being selected from the solution control for solving.…”
Section: Solver Settingsmentioning
confidence: 99%
“…The performance of SST is studied and analyzed in many engineering applications. Shear stress transport turbulence model was also used by Kumar and Chidambaram (2018) for the study on triangular tabs with corrugations. The potential core length for the simulation with the SST model and the experiment was as close as 0.87 and 0.88 D e , respectively.…”
Section: Study On Turbulence Modelsmentioning
confidence: 99%
“…The locations/placements of the corrugations on a triangular tab were also varied and studied numerically and experimentally by researchers in the recent times. Numerical comparison of the semicircular corrugated triangular tab with plain triangular tab to control the subsonic jet is investigated by Kumar and Chidambaram (2018), who found that the tab with corrugations yielded better effectiveness. Investigations by Kumar and Chidambaram (2019) on the corrugation locations by differing the spacing of the locations on the triangular tab to control the supersonic jet yielded more accurate results in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…For the co-flow nozzle, no slip wall condition is chosen. The governing equations are converged to a minimum error of 10 À4 (Sathish Kumar and Chidambaram, 2018).…”
Section: Numerical Detailsmentioning
confidence: 99%